Toxicological Evaluation of Certain Veterinary Drug Residues in Food : Seventieth Meeting of the Joint FAO/WHO Expert Committee on Food Additives. (WHO Food Additives, No. 61., 2009)
This volume contains monographs prepared at the seventieth meeting of the Joint FAO/WHO Expert Committee on Food Additives (JECFA), which met in Geneva, Switzerland, from 21 to 29 October 2008.The toxicological monographs in this volume summarize data on the veterinary drug residues that were evaluated toxicologically by the Committee: the antimicrobial agents avilmycin and tylosin, the antimicrobial agent and containment malachite green, the production aid melengestrol acetate, and the antimicrobial agents and production aids monesin and narasin.This volume and others in the WHO Food Additive.